Cardiac surgery in patients with essential thrombocytosis: a report of three cases - Aydin, Ufuk; Ata, Filiz; Ay, Derih; Ata, Yusuf; Turk, Tamer; Yavuz, Senol (The European Research Journal, 2016)
Essential thrombocytosis has been classified as a chronic myeloproliferative disorder. Patients with essential thrombocytosis undergoing cardiac surgery are at increased risk for bleeding and thrombosis. However, the incidence and treatment for this condition are not well known.  There are profound implications of essential thrombocytosis in patients undergoing cardiac surgery with the use of cardiopulmonary bypass, where heparin is used for anticoagulation. We want to present successful cardiac surgery in three patients with essential thrombocytosis. Patients received hydroxyurea and antiagregant treatment preoperatively and the thrombocyte counts were lowered to reference ranges. There were no cardiac or systemic complications due to essential thrombocytosis during the postoperative period.